GE_GERICHTE C/13228/2016 vom 28. November 2016 - GE Cour de justice (2016)
DÉCISION D'IRRECEVABILITÉ ; CAS CLAIR ; ÉVACUATION(EN GÉNÉRAL) ; DEMEURE ; COMPENSATION DE CRÉANCES | CPC.257; CO.257.d; CO.120;